Coupled mathematical models for physical and biological nanoscale systems and their applications : Banff International Research Station, Banff, Canada, 28 August - 2 September 2016 /: Banff International Research Station, Banff, Canada, 28 August - 2 September 2016. ([2018]) - Unknown
No abstract available